Global, regional, and national burden of early-onset OA attributable to high BMI: 1990-2021 estimates and 2036 projections from the global burden of disease study. - Binbin Zhang; Bin Dou; Wenzuo Gu; Chuan Lu; Qi Yan; Dawa Zhaxi; Yu Wang; Jiale Xu; Kewen Li (PLoS ONE)
Objective High BMI is a critical risk factor for early-onset OA (diagnosed before age 55). This study aimed to analyze global trends in the age-standardized disability-adjusted life years rates (ASDR) attributable to high BMI from 1990 to 2021. Methods Data from the Global Burden of Disease 2021 (GBD 2021) study were analyzed to assess early-onset OA attributable to high BMI across 204 countries, 21 GBD regions, and 5 Socio-Demographic Index (SDI) tiers. Temporal trends in ASDR were quantified using the estimated annual percentage change (EAPC) and Joinpoint regression. Age-period-cohort models and decomposition analysis identified drivers of burden, while inequality was assessed using the Slope Index of Inequality (SII) and Concentration Index (CI). ARIMA models projected trends to 2036. Results The disease burden of early-onset OA attributable to high BMI increased significantly between 1990 and 2021. The DALYs for early-onset knee and hip OA rose by 203.01% and 170.12%, respectively, with average annual percentage changes (AAPC) of 1.39% and 1.40%. The age-period-cohort analysis indicated that DALYs risk increased with age and period, and later birth cohorts experienced a higher burden of early-onset OA attributable to high BMI. Decomposition analysis revealed that population growth was the primary driver of the rising disease burden. There were significant absolute and relative inequalities in the burden of early-onset OA attributable to high BMI, as measured by the SDI. Countries with higher SDI bore a greater burden. The SII demonstrated that the ASDR gap between countries with the highest and lowest SDI widened steadily from 1990 to 2021. Predictive analysis suggested that the burden of early-onset OA attributable to high BMI will continue to increase over the next 15 years. Conclusion From 1990 to 2021, the global burden of early-onset OA attributable to high BMI showed a consistent upward trend, with significant inequalities across countries. The disease burden is projected to grow further in the future.